Cardiac troponins for the clinical management of patients with claudication and without cardiac symptoms - Mouselimis, Dimitrios; Hagstotz, Saskia; Lichtenberg, Michael; Donas, Konstantinos P.; Heinrich, Ulrike; Avranas, Konstantinos; Dimitriadis, Zisis; Blessing, Erwin; Langhoff, Ralf; Frey, Norbert; Katus, Hugo; Korosoglou, Grigorios (Journal of Clinical Medicine, 2022)
Many patients with peripheral arterial disease (PAD) exhibit undiagnosed obstructive coronary artery disease. We aim to identify the patients with lifestyle limiting claudication due to PAD and without cardiac symptoms, requiring coronary revascularization based on high-sensitive troponin T (hsTnT) values. ...
Gesehen am 09.11.2023